2021
DOI: 10.3390/horticulturae7110478
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmospheric CO2 Levels for Maintenance of Fruit Weight and Nutritional Quality upon Long-Term Storage in Blueberry (Vaccinium corymbosum L.) ‘Liberty’

Abstract: Blueberry fruits have gained consumer attention in recent years due to their good taste and high nutritional value. However, the short shelf-life of the fruit is one of the main downsides in intensive blueberry production. Therefore, optimized storage technology with a modified atmosphere is necessary to prolong blueberry fruit quality on the market. The aim of this study was to investigate long-term storage of fruit of the highbush blueberry (Vaccinium corymbosum L.) ‘Liberty’ under the air control (0.5% CO2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Although the total amount of organic acids decreased in blueberry during storage, the changes were not consistent between the four kinds of acids. These change differences in organic acids were also reported in other highbush blueberry cultivars during storage ( Smrke et al., 2021 ; Dragišić Maksimović et al., 2022 ). Dragišić Maksimović et al.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the total amount of organic acids decreased in blueberry during storage, the changes were not consistent between the four kinds of acids. These change differences in organic acids were also reported in other highbush blueberry cultivars during storage ( Smrke et al., 2021 ; Dragišić Maksimović et al., 2022 ). Dragišić Maksimović et al.…”
Section: Discussionsupporting
confidence: 83%
“…Although the total amount of organic acids decreased in blueberry during storage, the changes were not consistent between the four kinds of acids. These change differences in organic acids were also reported in other highbush blueberry cultivars during storage (Smrke et al, 2021;DragisǐcḾ aksimovićet al, 2022). DragisǐćMaksimovićet al (2022 found that the total acids, citric acid, malic acid, and shikimic acid in 'Bluecrop' and 'Liberty' blueberry showed the decline in varying degrees with the elongation of the storage period, while quinic acid content was no significant change.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…During storage, weight loss in fruit can occur because of postharvest decay, water loss, or physiological breakdown, indicating fruit quality deterioration (Smrke et al., 2021). The 2‐week stored haskap did not have a fruit weight significantly different from the fresh haskap ( a = 0.05), suggesting visual retention of quality for the 2 weeks fruits were held in cold storage before distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Bulk TA also decreased for 2-week stored haskap, while the SSC stayed consistent with the fresh haskap (Table 1). This corresponds to an increased • Brix/acid ratio during storage (Leisso et al, 2021), which is favorable for consumers, as a higher • Brix/acid ratio means the fruit will taste sweeter (Smrke et al, 2021). This was supported by one participant mentioning at the time of consumer testing, "this fruit (2-week stored haskap) seemed a little sweeter than the original haskap from week 1!"…”
Section: Relationships Between Consumers' Scores and Instrumental Datamentioning
confidence: 91%